Coeloglossum viride var. bracteatum extract attenuates Aβ-induced toxicity by inhibiting RIP1–driven inflammation and necroptosis. (10th January 2022) - Li, Xi-Xi; Lang, Xiu-Yuan; Ren, Teng-Teng; Wang, Jun; Lan, Rongfeng; Qin, Xiao-Yan
Abstract: Ethnopharmacological relevance: Tibetan ginseng named Wangla (tuber of Coeloglossum viride var. bracteatum ) is a traditional tonic that has Yang-strengthening and qi-enhancing, tranquilizing, intelligence-enhancing and longevity-enhancing properties. It has been used to treat impotence, spermatorrhea, anemia and insomnia. Therefore, its characteristic components and neuronal modulating effects were studied. Aim of the study: To investigate the elimination of Aβ-induced toxicity by CE and to elucidate the molecular mechanisms involving BDNF, FGF2, and their related signaling axis, and the RIP1-driven inflammatory pathway. Materials and methods: We established Aβ-induced toxicity models in cultured neurons and ICR mice, respectively. MWM and fear conditioning tests were performed for behavioral analysis of cognitive functions in mice. Western blot was used to investigate the levels of BDNF, FGF2, and their downstream effector TrkB/Akt/Bcl-2, as well as the RIP1-driven RIP1/RIP3/MLKL pathway. Immunofluorescence assay is used to examine the status of glial cells. Results: CE abrogated Aβ toxicity and inhibited apoptosis in cultured neurons, mainly by regulating the BDNF, FGF2, and TrkB/Akt signaling pathways as well as RIP1-driven inflammation and necroptosis. Similarly, mice injected intracerebrally with Aβ exhibited cognitive deficits and had elevated oxidative stress and inflammatory factors detected in their serum and brain. However, CE-treated mice showed recovery of cognitive abilities and quelled levels of oxidative stress and inflammatory factors. Moreover, Aβ toxicity led to a reduction in BDNF, FGF2, and related signaling regulators in the hippocampus and prefrontal cortex, accompanied by activation of RIP1-driven inflammatory signaling pathways, and a reduction in TBK1 and Bcl-2. However, CE restored the levels of BDNF, FGF2, and TrkB/Akt signaling pathway, while inhibiting RIP1-induced RIP1/RIP3/MLKL pathway, thereby antagonizing apoptosis and maintaining neuronal activity. Conclusions: CE effectively eliminated the toxicity of Aβ in cultured neurons and mouse models, which holds promise for drug development. Graphical abstract: Coeloglossum viride var. bracteatum extract (CE) eliminated the toxicity of Aβ, protected neuronal activity and restored cognitive function in mice. Image 1